2019
DOI: 10.3389/fmed.2019.00217
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Effect on Staphylococcus aureus—Platelet Interactions During Infectious Endocarditis

Abstract: Infectious endocarditis (IE) is a rare disease associated with high mortality and morbidity rate. The platelet–bacterial interaction presents the cornerstone of the development of endocardial vegetation. The epidemiology of IE has undergone profound changes between the last and the new decade, with Staphylococcus aureus becoming the main incriminated species. Despite improvements in antibiotic and surgical therapies, embolic disorders remain highly associated with IE that can be fatal. Antiplatelet drugs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 106 publications
(151 reference statements)
2
24
1
Order By: Relevance
“…In our study, we used an in vitro model focusing on the effect of antiplatelet agents on the platelet aggregation induced by bacteria. However, we are aware that evaluating the effect of these drugs considering other types of human cells, such as neutrophils and endothelial cells, in addition to platelets, may provide more information and better relate to in vivo conditions (Lubkin and Torres, 2016;Hannachi et al, 2019b). Further experimental and clinical studies are required to elucidate the distinct effects of antiplatelet drugs in the management of diseases related to bacterial-induced platelet aggregation, allowing targeted-antiplatelet treatment to be provided to selected patients and specific bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we used an in vitro model focusing on the effect of antiplatelet agents on the platelet aggregation induced by bacteria. However, we are aware that evaluating the effect of these drugs considering other types of human cells, such as neutrophils and endothelial cells, in addition to platelets, may provide more information and better relate to in vivo conditions (Lubkin and Torres, 2016;Hannachi et al, 2019b). Further experimental and clinical studies are required to elucidate the distinct effects of antiplatelet drugs in the management of diseases related to bacterial-induced platelet aggregation, allowing targeted-antiplatelet treatment to be provided to selected patients and specific bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococci and streptococci represent the most incriminated germs in IE (Park et al, 2016;Habib et al, 2019). The presence of protein receptors at the surface of these bacteria allows them to interact with platelets thereby promoting their aggregation (Ford et al, 1993;Hamzeh-Cognasse et al, 2015;Hannachi et al, 2019b). These platelet-bacteria interactions seem to be diverted in favor of bacteria despite the recognized immune role of platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recently the GLOBAL LEADERS trial has suggested that aspirin should be considered the preferred antiplatelet therapy for prevention of myocardial infarction and even ischaemic stroke 17 . Once ingested, aspirin is converted to salicylic acid (SAL) which is the metabolite responsible for the anti-inflammatory, antipyretic, and antithrombotic properties in humans 18 . Recently, we demonstrated that SAL strongly promotes S. aureus biofilm formation regardless of the methicillin susceptibility or clonal genomic characteristics 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that fibrin and microthrombi facilitate the interaction of bacterial surface adhesins with the extracellular proteins of an abnormal or damaged endothelium, there may be merit in platelet inhibition to prevent IE. 72 Indeed, in vitro studies suggest particular effectiveness against S. aureus and Enterococcus faecalis. 73 Similar effects are also observed with ticagrelor, whose antiplatelet activity interferes with platelet-leukocyte activity and whose major metabolite may have bactericidal activity.…”
Section: Risk Groups For Endocarditismentioning
confidence: 99%